2D Oxides Realized via Confinement Heteroepitaxy. (23rd November 2022) - Turker, Furkan; Dong, Chengye; Wetherington, Maxwell T.; El‐Sherif, Hesham; Holoviak, Stephen; Trdinich, Zachary J.; Lawson, Eric T.; Krishnan, Gopi; Whittier, Caleb; Sinnott, Susan B.; Bassim, Nabil; Robinson, Joshua A.
Abstract: Novel confinement techniques facilitate the formation of non‐layered 2D materials. Here it is demonstrated that the formation and properties of 2D oxides (GaOx, InOx, SnOx ) at the epitaxial graphene (EG)/silicon carbide (SiC) interface is dependent on the EG buffer layer properties prior to element intercalation. Using 2D Ga, it is demonstrated that defects in the EG buffer layer lead to Ga transforming to GaOx with non‐periodic oxygen in a crystalline Ga matrix via air oxidation at room temperature. However, crystalline monolayer GaO2 and bilayer Ga2 O3 with ferroelectric wurtzite structure(FE‐WZ') can then be formed via subsequent high‐temperature O2 annealing. Furthermore, the graphene/X/SiC (X = 2D Ga or Ga2 O3 ) junction is tunable from Ohmic to a Schottky or tunnel barrier depending on the interface species. Finally, using vertical transport measurements and electron energy loss spectroscopy analysis, the bandgap of 2D gallium oxide is identified as 6.6 ± 0.6 eV, significantly larger than that of bulk β‐Ga2 O3 (≈4.8 eV), suggesting strong quantum confinement effects at the 2D limit. The study presented here is foundational for development of atomic‐scale, vertical 2D/3D heterostructure for applications requiring short transit times, such as GHz and THz devices. Abstract : It is demonstrated that the formation and properties of 2D oxides at the epitaxial graphene/silicon carbide (EG/SiC) interface is dependent on the graphene buffer layer properties prior to element intercalation (Ga, In, and Sn). The graphene/X/SiC (X = 2D Ga or Ga2 O3 ) junction is tunable from Ohmic to a Schottky or tunnel barrier depending on the interface species. Finally, using vertical transport measurements and electron energy loss spectroscopy analysis, the bandgap of crystalline bilayer Ga2 O3 with ferroelectric wurtzite structure is identified as 6.6 ± 0.6 eV, significantly larger than that of bulk β‐Ga2 O3 (≈4.8 eV).